France : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This paper describes economic developments in France during the 1990s. The recovery of activity that took hold in the second half of 1993 slackened markedly in early 1995. The slowdown was initially evident in domestic demand, particularly private consumption. This was followed by a weakening in exports, private nonresidential investment, and stock building, which became more pronounced toward the end of the year. The strikes of December 1995 had a further-albeit temporary-negative effect on output in the fourth quarter. Overall, real GDP grew by only 2.2 percent in 1995.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet